2006
DOI: 10.1038/nrd2144
|View full text |Cite
|
Sign up to set email alerts
|

Innovative lead discovery strategies for tropical diseases

Abstract: Lead discovery is currently a key bottleneck in the pipeline for much-needed novel drugs for tropical diseases such as malaria, tuberculosis, African sleeping sickness, leishmaniasis and Chagas disease. Here, we discuss the different approaches to lead discovery for tropical diseases and emphasize a coordination strategy that involves highly integrated partnerships and networks between scientists in academic institutions and industry in both wealthy industrialized countries and disease-endemic countries. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
409
0
18

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 494 publications
(435 citation statements)
references
References 54 publications
8
409
0
18
Order By: Relevance
“…Interestingly, the toxicity of the NQC-AmpB system was approximately 10 times less than that of free AmpB. In addition, the selectivity index (SI), an indicator of the selectivity of drugs tested in in vivo models (60) , was increased by 10-fold when AmpB was added to the proposed nanodelivery system. Because the nanoparticle formulations did not cause any hemolysis of human red blood cells (31) (Table 1), the study suggested that the NQCAmpB nanoparticles could be used as an AmpB delivery system to be evaluated in in vivo models against Leishmania spp.…”
Section: Optimized Nanoparticle Delivery Systems For Ampb Based On Chmentioning
confidence: 87%
“…Interestingly, the toxicity of the NQC-AmpB system was approximately 10 times less than that of free AmpB. In addition, the selectivity index (SI), an indicator of the selectivity of drugs tested in in vivo models (60) , was increased by 10-fold when AmpB was added to the proposed nanodelivery system. Because the nanoparticle formulations did not cause any hemolysis of human red blood cells (31) (Table 1), the study suggested that the NQCAmpB nanoparticles could be used as an AmpB delivery system to be evaluated in in vivo models against Leishmania spp.…”
Section: Optimized Nanoparticle Delivery Systems For Ampb Based On Chmentioning
confidence: 87%
“…Only those compounds that attain an SI value greater than 50 (Nwaka & Hudson 2006) will be considered for further screening. Next, a single drug concentration equivalent to 50X the parasite IC 50 of each compound will be assayed using the AlamarBlue TM protocol to evaluate the toxicity to mammalian cells (Appendix B).…”
Section: For In Vitro Models For Chagas Disease Drug Discovery and Dementioning
confidence: 99%
“…An agreed set of product profiles that describe the target clinical efficacy, route of administration, dosage regimen, safety and cost of treatment are widely used in industry to drive lead discovery and candidate selection. Emphasis should be placed on understanding the product profile of drugs required for the various neglected diseases 3 .…”
Section: Global Portfoliomentioning
confidence: 99%
“…The TDR is now implementing a scalable, collaborative model for drug discovery that is based on networks and partnerships with industry and academia in developed and developing countries 3 . Scaling up or expanding innovative drug-discovery networks could be a way to mobilize resources from both public and private sectors.…”
mentioning
confidence: 99%